Calidad de servicio y satisfacción del cliente en la agencia de viajes y tour operador Iquitos Experience Tours E.I.R.L. de la ciudad de Iquitos, 2024 - Pinedo Zevallos, Nelson Ricardo (2025)
Title: Quality of service and customer satisfaction in the travel agency and tour operator Iquitos experience tours E.I.R.L. of the city of Iquitos, 2024. The objective: To determine the relationship between service quality and customer satisfaction in the Travel Agency and Tour Operator Iquitos Experience Tours E.I.R.L. in the city of Iquitos, 2024. Methodology: correlational, descriptive, non-experimental design research. The sample: 150 clients of the agency participated Results: Customers rated the quality dimensions with a good level: reliability 24.6%, responsiveness 50.7% and safety 63.3%. Of the total, regarding the dimensions of satisfaction, they rated with a good level: 40.7% to expectation, 43.4% to perception and 30.0% to empathy. The dimensions: reliability has a highly positive relationship with expectation, perception and empathy (p=0.000). Responsiveness is highly related to expectation and perception (p=0.001, p=0.000 respectively), and security is related to perception (p=0.000). It is concluded that there is a relationship between the quality of service and the satisfaction of the Client in the Travel Agency and Tour Operator Iquitos Experience Tours E.I.R.L.